A Comparative Research on the Effectiveness of Progressive versus Proportional Tax Systems in Enhancing Social Justice - Syahril, Muh. Akbar Fhad; Hasan, Hamida (Administrative and Environtmental Law Review, 2024)
This research investigates the effectiveness of progressive and proportional tax systems in promoting social justice from the perspectives of tax law and accounting. Each system presents its own advantages and disadvantages. While progressive taxation is considered more vertically equitable, it may induce economic distortions—inefficiencies that disrupt market dynamics and prevent economic agents from maximizing social welfare. In contrast, proportional taxes are simpler and more efficient but are less equitable in their distribution of the tax burden. This study identifies critical challenges, including weak law enforcement characterized by inconsistent application of laws and a tendency for those in power to evade accountability, as well as low taxpayer compliance and discrepancies between tax law and accounting standards. To achieve optimal social justice, this research advocates for a hybrid approach that integrates elements from both tax systems, harmonizes regulations, and enhances taxpayer compliance through improved law enforcement and public education initiatives.